Factors Affecting Workforce Agility Among Government-aided Secondary School Teacher - Lim, Yi Shern (2021)
On the verge of leaping into the 3rd transformation wave of the Malaysian Education Blueprint (MEB) 2013-2025, flexibility is found to be one of the key features to achieve excellence in Malaysian education system. With the scarcity of literature on workforce agility, this quantitative study aspired to explore this concept among normal academic teachers in government-aided secondary schools from the viewpoint of Self Determination Theory. Further, other variables such as digital competency, employee empowerment, and knowledge sharing, were also studied in the attempt to find their significance in influencing workforce agility of the teachers. To add novelty into this research, social media usage was also tested for its moderating effect on the hypothesized interactions. Data collected from the respondents was derived from 217 teachers in the Larut Matang and Selama district in Perak through questionnaires distributed. The research model explained 59.1 percent of workforce agility. From the analysis through the disjoint 2-stage approach with PLS-SEM, the exogenous variables such as digital competency, employee empowerment, and knowledge sharing, were found to be influencing the endogenous construct, while all hypothesized moderated relationships were not supported in this study. Interestingly, it is also revealed that social media usage, instead, has a direct influence onto workforce agility. The limited responses, yet derived only from a district, is not suffice to reflect the characteristics of the teachers throughout the country. Being a single-sourced data, thus, the perspective from the school leaders and middle managers on workforce agility remains unknown.